The Impact of Foreign Direct Investment on Economic Growth in Zambia: A Comprehensive Analysis - Tryson Yangailo (Revista Científica Profundidad Construyendo Futuro)
This study examines the relationship between economic growth, government consumption expenditure, gross national income (GNI) per capita, exports and foreign direct investment (FDI) in Zambia from 1994 to 2023. Using secondary data from the World Bank and regression analysis using Jamovi software, the study finds significant positive impacts of GNI per capita, exports and FDI on Zambia's GDP. The findings underscore the critical role of FDI in driving economic growth through technology transfer, managerial expertise and capital formation, while emphasising the importance of macroeconomic stability and diversified economic policies to maximise the benefits of FDI. The findings provide valuable insights for policymakers in formulating strategies to leverage FDI for sustainable economic growth in Zambia.